Preparação e caracterização de óxido de alumínio anodizado sobre substratos transparentes - Domenici, Natália Virag [UNESP] (2015)
In this work, it is presented the preparation of thin films of Al2O3 by anodization using the electrolyte solution containing ethylene glycol and tartaric acid. The Al2O3 films were grown by anodization of aluminum films previously deposited by vacuum evaporation on two types of substrates, glass and ITO using constant current of 0,63 mA/cm2. Al2O3 films on glass with thickness variation of the residual aluminum layer, and Al2O3 films with 10 nm residual layer of aluminum on ITO were obtained in order to have possible applications in transparent devices. The films were characterized by capacitance measurements and dielectric loss versus frequency, atomic force microscopy (AFM) and optical transmittance. The results show that the dielectric constant obtained for the oxides are between 5.4 and 7-8 and is from 5,10x10-3 and 1,4x10-2. The dielectric constant values depend on the oxide surface roughness and AFM images show that this depends on the roughness of evaporated aluminum. From the optical transmittance spectra, it was found that the oxides obtained with a residual layer of 20 nm of aluminum have a transmittance of 80%